Poverty in education across the UK : a comparative analysis of policy and place - Ivinson, Thompson; Ivinson, Gabrielle (Policy Press, 2020)
The nuanced interconnections of poverty and educational attainment across England, Scotland, Wales and Northern Ireland are explored in this unique analysis. Experts investigate how different educational structures and policies affect teachers' engagement with marginalised groups and consider how inequalities might be reduced.